Nivel de conocimiento en residuos sólidos y actitudes ambientales en pobladores del asentamiento humano “Aeropuerto” distrito de San Juan. 2023 - Reategui Ushiñahua, Maria del Carmen (2024)
The objective of this research work was to study the relationship between the level of knowledge about solid waste and the environmental attitudes that the residents of the AAHH Airport have in the year 2023. The research, due to its approach, was quantitative, prospective, at a relational level. simple, non-experimental research design. The target population of the study was made up of the residents of the AAHH Airport, in the year 2023. The sample was made up of 97 residents who were present at the time of the application of the data collection instrument, the technique used was The survey and the instruments applied were two questionnaires of 10 items each, the same one that passed the validity and reliability tests. The data obtained were analyzed taking into account the objectives and research hypothesis and expressed in a Basic Data Matrix (MBD) and analyzed, processed and tabulated through the statistical package SPSS version 27. The main results expressed that there are mostly levels of low and regular knowledge and favorable environmental attitudes predominated. An indirect and intense relationship was found between both variables at a 0.05 probability, making it necessary for municipal institutions, whether district or provincial, to take action regarding this issue.